Entrepreneurial intention have influenced by entrepreneurship education, entrepreneurial skills through entrepreneurial motivation: a study on Jambi university students - Suratno Suratno; Hidayatul Arief; Yantoro Yantoro (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Entrepreneurs are economic heroes for the country, entrepreneurs not only help provide jobs for the unemployed but entrepreneurs also pay taxes to the state as a source of state revenue. Therefore, the state really needs the presence of entrepreneurs to encourage the development and progress of the nation. This study aims to describe and how the influence of entrepreneurial education (EE) variables, skills of marketing (SM), in growing entrepreneurial intention (EI) through motivation towards entrepreneurship (ME). The population of this research is students participating in the July 2021 graduation from all existing faculties at Jambi University, especially undergraduate study programs. Data collection was carried out using a questionnaire adapted from previous researchers. The collected data were analyzed using a structural model approach with hypotheses to be tested with the help of the SPPS and SmartPLS programs. The results of the study show that all the variables studied influence entrepreneurial intentions, both direct and indirect through entrepreneurial motivation. The implication is that entrepreneurship education not only strengthens entrepreneurial motivation but also strengthens entrepreneurial skills because both will strengthen motivation and ultimately foster entrepreneurial intentions.